Liniowa interpolacja procesu Wienera : przykłady zastosowań wzoru Ito - Posacka, Katarzyna (Linearly Interpolated Wiener Process : Some Applications of the Ito Formula, 2006)
The main purpose of this paper is to present definition and linearly interpolated Wiener process. In part 3 one- and multi-dimensional version of the Ito formula is shown, which can be used for stochastic differential equations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 140-146